Apo B genetic variants that modulate postprandial lipoprotein metabolism - Talmud, P; Peacock, R; Karpe, F; Hamsten, A; Humphries, S (1996)
We conducted a pilot study to examine the influence of common genetic variation in the apolipoprotein B gene on postprandial Lipid and lipoprotein metabolism, in a group of 30 individuals who had survived a myocardial infarction before the age of 45 (normo- and hypertriglyceridemic patients) and 11 age-matched healthy individuals. Postprandial lipid or lipoprotein levels were examined by apolipoprotein B signal peptide genotype in the three separate groups, and after adjustment for fasting triglycerides in the whole group combined. For the signal peptide polymorphisms individuals with one or more SP24 allele had a 38% smaller mean area under curve (P = 0.06) for postprandial large chylomicron remnants and a 29% smaller mean area under curve (P = 0.02) for large, very low density lipoproteins compared to individuals homozygous for the wild type signal peptide 27 allele. This difference was due to a slower increase of these lipoproteins in the early postprandial period in carriers of the signal peptide 24 allele (6.5 mg/L/hr versus 15 mg/L/hr for homozygosity for the signal peptide 27 allele). These results lend support to our yeast expression studies of fusion proteins of apolipoprotein B signal peptide isoforms and yeast invertase; compared to the signal peptide 27, the signal peptide 24 mediated inefficient translocation into the endoplasmic reticulum and was secretion defective. Expression studies of apolipoprotein B signal peptide variants in mammalian cells are underway. Thus this pilot suggests that the apolipoprotein B signal peptide alleles confer a functional difference on apolipoprotein B secretion that is reflected in the postprandial state.